(3QMdGJ LGf Oj Jjajfh aj GdCfGVhd hGdYQGb hGdNdjL GdYQHj (B(1664-1665) /s - (3Oj Jjajfh, LGfs 1633-1667; (3eMehO, CfjS YHO GdNGdbs ((3HjQhJ(B:s (3GdeDSSI GdYQHjI ddOQGSGJ hGdfTQ,s, 2013)
(3JJejR GdQMdGJ GdaQfSjI HfcgI COHjI QajYI bO JNdh efgG cKjQ ef GdQMdGJ GdCNQi(B. (3hQMdI GdSjO LGf Pj fjajfh Edi GdTQb (B(1667-1663) (3hGMOI ef GdQMdGJ PGJ GdbjeI GdJGQjNjI hGdLZQGajI hGdeYQajI GdcHjQI, hgj ef GdQMdGJ GdbdjdI GdJj TedJ efGWb hGSYI ef GdYGde GdYQHi aj Jdc GdeQMdI, ceG CfgG ef GdeQGLY GdegeI aj JGQjN efWbI dG JRGd eYdheGJfG YfgG ZGeVI hefbhVI(B.s
(3JUeje GdZdGa (B: (3Ojeh HQS ; GdUa GdVhFj (B: (3GdeDSSI GdYQHjI ddOQGSGJ hGdfTQ ; GdJfajP GdWHGYj (B: (3Ojeh HQS(B.s
Keywords: (3GdYQGbs -- (3hUa hQMdGJs -- (3bQf (B17s; (3Ohd GdNdjL GdYQHjIs -- (3hUa hQMdGJs -- (3bQf (B17s; (3BSjG GdUZQis -- (3hUa hQMdGJs -- (3bQf (B17s